Teknik Forensika Digital untuk Investigasi Pesan Sekali Lihat (View Once) pada Aplikasi Instant Messenger - Ramadhan, Gilang; Prayudi, Yudi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The popularity of Instant Messaging apps encourages developers to improve features and security, especially data privacy. However, these improvements also potentially bring risks to users. One of the most popular new features is ‘one-look messages’ to maintain sender privacy. This feature allows messages to disappear once viewed, irrevocably and has been implemented on apps such as Snapchat, Instagram, and WhatsApp. The purpose of this research is to provide a reference on the reliability of digital forensic Tools in uncovering cybercrime. Thus, it is expected that the digital evidence obtained has strong integrity, reliability and legality to be used in the legal process. This research adopts the framework of the National Institute of Standards and Technology (NIST) and analyzes a cybercrime scenario in the form of sending files using the one-look message feature, utilizing the Magnet Axiom digital forensics tool. This research also uses a smartphone with root conditions that have Snapchat, Instagram and WhatsApp applications installed. The results of this study show that with a root smartphone, the use of Axiom magnet forensic Tools is able to acquire and analyze files sent using the one-look feature and obtain 13 digital evidence from 18 scenarios created. There is not much research that discusses the latest features of Instant Messaging applications, with this paper it can provide a little description of the Sekalin see feature and can be developed in the next paper.